The Essence of Consumer Lending in Modern Russia ("Journal "U". Economy. Management. Finance.", 2021)
The concept of consumer lending through the eyes of domestic and foreign researchers is presented. The concepts of subjects of credit relations according to the legislative aspects of the Russian Federation are given. The basic principles used by credit organizations are considered. At the final stage, the functions of lending are disclosed. Conclusions on the work are made.
Keywords: consumer credit; interest rate; bank; borrower; lender; lending principles